Upaya Meningkatkan Aktivitas Belajar Siswa dalam Pembelajaran IPD dengan Metode Diskusi di Kelas VII.F SMP Negeri 12 Mataram - Muhsiniadi, Muhsiniadi (ANWARUL, 2023)
This study aims: to determine the increase in student learning activity in social studies learning with the discussion method in Class VII.F of SMP Negeri 12 Mataram in the 2022/2023 academic year. This research was designed using Classroom Action Research. The subjects in this study were class VII.F students of SMP Negeri 12 Mataram, totaling 32 people, consisting of 16 female students and 16 male students. While the research procedure goes through the stages of Planning, Action Implementation, Observation, and reflection. The results showed that: Data on student learning outcomes in IPS learning using discussion mode increased from the initial data obtained 65.63% classical completeness, increased to 71.88% in cycle I, to 81.25% in cycle II to 100% in cycle III. So student learning outcomes in social studies learning using the discussion method conducted by the teacher are very good. Teaching and learning activities carried out by the teacher experienced an increase from the acquisition of a score of 26 (72.23%) in cycle I, to 29 (80.56) in cycle II, to 32 (88.89) in cycle III. Student learning activities, it can be described that the average percentage in the first cycle is 66.67%. But in cycle II, student learning activities increased to 77.78% in cycle III, and to 86.11%. So student learning activities in social studies learning are good.